Pengaruh Efficient Market Hypothesis, Gambler’s Fallacy, Familiary Effect, Risk Perception, dan Faktor Ekonomi Terhadap Keputusan Investasi - Sucitra Dewi (Economics, Business and Management Science Journal, 2022)
This study show to prove the effect of the efficient market hypothesis, gambler's fallacy, familiarity effect, risk perception, and economic factors on investment decisions. This research is quantitative research with associative approach. All capital market investors in Medan are the population in this study. The sample was determined using judgment sampling technique and Malhotra theory so that 270 samples were obtained. Multiple linear regression analysis was used to analyze this research. The results of the multiple linear regression analysis show that the efficient market hypothesis, gambler's fallacy, familiarity effect, risk perception, and economic factors partially have a positive and significant effect on investment decision making. Other results are efficient market hypothesis, gambler's fallacy, familiarity effect, risk perception, and economic factors simultaneously have a positive and significant effect on investment decision making.